Mesocoelium Odhner, 1901 (Digenea: Mesocoelidae) revisited; a revision of the family and re-evaluation of species composition in the genus - Dronen, Norman O.; Calhoun, Dana M.; Simcik, Steven R. (Zootaxa, 2012)
The family Mesocoelidae Dollfus, 1929 is revised supporting the recognition of Pintneria Poche, 1907 where the testesare tandem and Mesocoelium Odhner, 1910 where the testes are oblique to nearly side by side. Nine basic body types aredefined within Mesocoelium of which four contain only a single species the: zhejiangensis body type represented by Me-socoelium zhejiangensis Xida & Puzhu, 1986; pesteri body type represented by Mesocoelium pesteri Saoud, 1964; brienibody type represented by Mesocoelium brieni Vercammen-Grandjean, 1960; and carli body type represented by Mesocoe-lium carli André, 1915. Keys to species are proposed for the remaining five body types the: lanceatum; mesembrinum;monas; sociale; and leiperi body types. The characteristics used to separate the nine body types and those used in the fiveproposed keys to species are discussed. Mesocoelium zhejiangensis, Mesocoelium cameroonensis Saoud, 1964, Mesocoe-lium meggitti Bhalerao, 1927, Mesocoelium monodi Dollfus, 1929 and Mesocoelium americanum Harwood, 1932 are re-described and Mesocoelium neohylae n. sp. is described. We consider Mesocoelium leptobotiae Pu-qin, 1981 to besynonymous with Mesocoelium burdwanenesis Mukherjee, 1968; Mesocoelium magniovum Wang, Sun, Zhao, Zhang &Wang, 1985, Mesocoelium micreatum Park, 1939, Mesocoelium minutum Hua, 1986 and Mesocoelium tritoni Matskási,1990 to be synonymous with Mesocoelium brevicaecum Ochi, 1929; Mesocoelium elongatum Goto & Ozaki, 1929, Me-socoelium ovatum Goto & Ozaki, 1930 and Mesocoelium pearsei Goto & Ozaki, 1930 to be synonymous with Mesocoe-lium lanceatum Goto & Ozaki, 1929; Mesocoelium marrsi Fernando, 1933 to be synonymous with Mesocoelium burtiFernando, 1933; Mesocoelium travassosi Pereira & Cuocolo, 1940 to be synonymous with M. meggitti; Mesocoeliumasymmetrovitellarius Kumari & Verma, 1992 to be synonymous with Mesocoelium melanostictii Rao, 1989; and Meso-coelium varunae Baugh, 1957 and Mesocoelium dolichenteron Richard, 1965 to be synonymous with Mesocoelium sociale (Lühe, 1901).